Customer Churn Analysis: Analyzing Customer Churn Determinants on an ISP Company in Indonesia - Nisrina Salma; Atik Aprianingsih, Ph.D (Buletin Pos dan Telekomunikasi, 2021)
The growth of Internet Service Providers (ISP) in Indonesia, has led Indonesia to be one of the world’s fastest-growing telecommunications market. This condition derives a number of internet service providers pushing the Indonesian market massively one of them is HELOSEL (pseudonym). With this condition, ISP can suffer from a loss of valuable customers to competitors due to many attractive offers from the competitions or known as customer churn. Customer churn is one of the most pressing challenges in today's fast-paced and challenging telecom industry. The trend of customer churning in HELOSEL is increasing from month to month during the year of 2020 with the average churn rate of each month is 6,48%. To retain the HELOSEL customers’, company needs to know what kind of factors that could possibly affect the customer from churning. Hence, knowing the customer churn determinants in HELOSEL is essential for to prevent customer churn.